Planning of Educational Actions by the Multidisciplinary Team of the Family Health Strategy - Vieira de Andrade, Ana Carolina; Tessmann Schwalm, Magada; Bisognin Ceretta, Luciane; Santina Dagostin, Valdemira; Soratto, Maria Teresa (O Mundo da Saúde, 2013)
The objective of the research was to identify how the health education actions are planned by the multidisciplinary team at the Family Health Strategy. A qualitative study was conducted in the Family Health Strategies belonging to a health regional with a sample of eight nurses who are managers of these units. The difficulties to develop educational activities are related to team commitment, community membership, lack of human, material and financial resources and lack of support from managers. Constant improvement of knowledge and professional practice to develop health education actions is essential.